The Effect of Melting Temperature Variations on Casting Aluminum Waste to The Hardness - Ah. Sulhan Fauzi,Irwan Setyowidodo,Erlangga Aji Dinata,Aditya Mahendra (International Conference on Industrial Revolution for Polytechnic Education, 2020)
This research is motivated by the number of aluminum waste which is a problem that must be considered. there is also an increasing number of needs for aluminum from producers and consumers to be used as raw materials in making tools for everyday life which continue to increase every years. It is necessary to recycle aluminum waste to reduce waste problems and reduce the cost of making aluminum raw materials, one of them is the casting process. In the casting process, to note is the melting temperature is very important because it will affect the quality of the mechanical properties of aluminum produced by casting. From this reason, the formulation of the problem in this research is how the influence of the temperature variation of melting on the casting of aluminum waste on the hardness of aluminum from casting results. In this study the temperature variation for melting process was 660 ºC, 680 ºC, 700 ºC, 720 ºC, 740 ºC. After the melting temperature variations were carried out on casting aluminum waste, then the results of the specimens were tested for Rockwell hardness to determine the hardness value of casting aluminum from the melting temperature variation. The test results show that the melting temperature variations affect the hardness value of aluminum as evidenced by the analysis of the research data, indicating that an increase in melting temperature will reduce the hardness of aluminum. It is proven that on the highest melting temperature, 740 ºC which has the lowest hardness value, 98.9 RHB (Rockwell Hardness number type B) and the highest hardness value reaches 112.9 RHB with a melting temperature of 660 ºC.